Aerosolised iloprost improves pulmonary haemodynamics in patients with primary pulmonary hypertension receiving continuous epoprostenol treatment. Issue 9 (1st September 2001) - Petkov, V; Ziesche, R; Mosgoeller, W; Schenk, P; Vonbank, K; Stiebellehner, L; Raderer, M; Brunner, Ch; Kneussl, M; Block, L H
Abstract : BACKGROUND: Continuous intravenous treatment with epoprostenol significantly improves pulmonary haemodynamics and survival in patients with primary pulmonary hypertension (PPH). Its beneficial effect, however, may be blunted due to adverse effects such as catheter sepsis and systemic hypotension. Recent investigations have shown that inhaled iloprost is effective in the treatment of PPH. Based on their different pharmacokinetics, we hypothesised that the combination of intravenous epoprostenol and inhaled iloprost would be more efficacious than epoprostenol alone during acute testing in patients with PPH. METHODS: The effect of a single dose of inhaled iloprost (30 μg total over 15 minutes) on pulmonary haemodynamics was examined in eight patients with PPH (initial non-responders to nitric oxide) who had considerable adverse effects during treatment with epoprostenol. RESULTS: The combination of inhaled iloprost and intravenous epoprostenol significantly improved mean pulmonary artery pressure (MPAP), cardiac index (CI), mixed venous oxygen saturation (Svo 2 ), and systemic arterial oxygen pressure (Pao 2 ) compared with epoprostenol treatment alone. Mean systemic arterial pressure (MSAP) and pulmonary capillary wedge pressure (PCWP) remained unchanged. CONCLUSIONS: The pulmonary vasoreactivity shown by additional iloprost inhalation during effective epoprostenol treatment suggests that an improvement of treatment for pulmonary hypertension may be possible by combining vasoactive substances.